Processo de desenvolvimento de capacidades dinâmicas em organizações do setor hospitalar - Lazarotto, Elizabete Casagrande (2017)
The dynamic capabilities aim to explain how do the organizations reach and sustain the competitive advantages throughout the times, in situations of fast and unpredictable changes, characterized as dynamic environments. In such context, the dynamic capabilities combine the dynamics of the environment to the internal elements of the organization and, therefore, it is crucial to comprehend how are developed these capabilities in organizations with dynamic environments. In face of these factors, this thesis aimed to comprehend the process of developing dynamic capabilities in hospital organizations set up in dynamic environments. For that, it was based on the model proposed by Wang and Ahmed (2007) for the study of dynamics and absorptive and innovation capabilities, which are factors that compose the dynamic capabilities. For analyzing the development process of each of these capabilities, through elements and mechanisms, it was used the study of Camargo and Meirelles (2012). As for the method, it was conducted a qualitative, exploratory and descriptive research, through a multiple case study in two hospital organizations in Passo Fundo - RS. Data were collected through the analysis of documents and structured interviews applied with administrators that occupy strategic positions in the organizations. Such data were analyzed through the content analysis, with the support of the software Altas/TI, used in the analysis of qualitative research. Results identified that the dynamics of the elements in the environment affects the process of developing dynamic capabilities, characterized, in this study, by the absorptive and innovation capabilities. Such process occurs in behaviors and abilities found in the organizations by accepting changes, encouraging and comprehending them as usual. These changes are supported by processes and routines and sustained by the mechanism of learning and managing of the knowledge, which are articulated. These elements and mechanisms were identified in each dimension of the absorptive and innovation capabilities in the investigated hospitals, showing the similarity in the process of developing dynamic capabilities in both hospitals.